Comprehensive Assessment of Air, Soil, and Water Pollution for Environmental Health in Al-Hai City, Iraq - Al Rukabie, Jamal; Ali, Ali Sabeeh (University of Thi-Qar Journal of Science, 2024)
Sustainability has evolved into a broad phrase that includes practically every aspect of life on the Earth, from local to global, and over different periods. Sustainable biological systems include healthy, long-lived forests and wetlands. This paper aimed to study and measure pollution indicators in the Al-Hai city center's air, soil, and water in Wasit province, located at Coordinates (32.1742 N° and 46.0433 E°). The data for Al-Hai city's ambient air pollutants (CO, NO, NO2, H2S, SO2, and CO2) that considered air pollution was recorded for the date (12-13/12/2021). The Maximum values for the concentration of carbon monoxide CO and sulfur dioxide SO2 were 1.019 ppm and 0.0321 ppm, respectively. The water and sediment samples were collected in December 2021, and all samples were analyzed in the laboratory. Heavy elements (Cd, Pb, As, and Hg) were measured in soil and water. The samples were collected and taken from two stations in the Gharraf River of Al-Hai city in Wasit province to investigate the potential for environmental damage caused by these components in this region. This study will be conducted at two stations (North and South of Al-Hai city center) beginning in December 2021. In the south station, all heavy elements showed exponential growth in water and sediment samples, but concentrations in the north station were low. The highest value recorded in this study was for the pb concentration in the soil samples taken from the main street, which was 31.9 ppm.